Melatonin and its physiological and therapeutic effects: A review - Stefanović Bojana V.; Spasojević Nataša M.; Ferizović Harisa N.; Janković Milica D.; Virijević Kristina M.; Dronjak Slađana S. (Kragujevac Journal of Science)
Melatonin, an evolutionarily old molecule, is found in many living organisms. This neurohormone is known to control many physiological processes, including circadian rhythm, mood, and behavior. Melatonin was discovered to be a direct free radical scavenger. By activating its receptors, it stimulates a wide range of signaling pathways. It has been proven that melatonin exerts neuroprotective and antidepressant like effects. Also, many researchers have found that melatonin plays an important role in various cardiovascular diseases. In the near future, melatonin will be a promising agent to control the fate of mesenchymal stem cells by regulating the generation of reactive oxygen species and the release of immune factors in regenerative medicine. Collectively, the studies link melatonin to a variety of outcomes and have a strong regulatory impact on numerous physiological processes in the body.